ChemInform Abstract: Intramolecular Heterocyclization and Cyclopalladation of Selenoanisole Substituted Propargyl Imines: Synthesis and Reactivity of Pd—C Bond Towards Alkynes. Issue 34 (26th August 2014) - Racharlawar, Shailesh S.; Shankar, D.; Karkhelikar, Manjusha V.; Sridhar, B.; Likhar, Pravin R.
Abstract The synthesis of dimeric cyclopalladated benzoselenophenes (II) is presented and their reactivity towards insertion of internal bisarylalkynes is studied.